Cellular and molecular portrait of eleven human glioblastoma cell lines under photon and carbon ion irradiation. Issue 1 (28th April 2015) - Ferrandon, S.; Magné, N.; Battiston-Montagne, P.; Hau-Desbat, N.-H.; Diaz, O.; Beuve, M.; Constanzo, J.; Chargari, C.; Poncet, D.; Chautard, E.; Ardail, D.; Alphonse, G.; et al.
Highlights This study provides consistent database of the cellular and molecular response of glioblastoma cells to photon irradiation. To the best of our knowledge it represents the largest archive for carbon ion hadrontherapy response of glioblastoma cells. This type of archive is intended to customize the treatment of patients. It will allow the development of new predictive mathematical models for the response of tumors to radiation. The database realized could ultimately improve hadrontherapy treatment plans.